The sage in relation: family in Ben Sira's house of discipline - Montanaro, Andrew (Deuterocanonical and Cognate Literature Studies, 2025)
The Jewish sage Ben Sira links the partnership of the sage with personified Wisdom to his overall teaching on marriage and family. This study provides a detailed analysis of this connection, first, by describing the overlapping characteristics of fathers in families and sages among their students as seen through an examination of Ben Sira's use of metaphorical family language, whereby the sage takes the role of father in the pedagogical setting. This study then describes the spousal relationship between the sage and personified Wisdom, particularly as it appears alongside the marital instructions in Sir 23:16-26:18. This study further considers Ben Sira's privileged social position to influence the religious conviction of next generation Judaism and to strengthen Jewish youth against rising Hellenistic pressures that may tempt them away from Torah adherence. Ben Sira's solution then is found in his proposed vision of families, modeled after his pedagogical setting. Finally, Ben Sira's teaching is compared to other Second Temple texts, showing the importance of his context for his conception of family and the needs of his time. Thus, this study shows the relevance of Ben Sira's teaching for families as well as his distinctiveness among other Jewish texts